Energetic responses of head-out water immersion at different temperatures during post-exercise recovery and its consequence on anaerobic mechanical power - Coertjens, M.; Coertjens, P. C.; Tartaruga, M. P.; Gorski, T.; Lima-Silva, A. D.; Carminatti, L. J.; Beyer, P. O.; de Almeida, A. P. V.; Geremia, J. M.; Peyré-Tartaruga, L. A.; Kruel, L. F. M. (European Journal of Applied Physiology, 2023)
Purpose While exercise recovery may be beneficial from a physiological point of view, it may be detrimental to subsequent anaerobic performance. To investigate the energetic responses of water immersion at different temperatures during post-exercise recovery and its consequences on subsequent anaerobic performance, a randomized and controlled crossover experimental design was performed with 21 trained cyclists.